PENGARUH STRUKTUR MODAL DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR CONSUMERNON-CYCLICALS YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Syukria Mardhatillah; Novera Martilova (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine and analyze how much influence capital structure and investment decisions have on firm value in manufacturing companies in the Consumer Non Cylicals sector listed on the IDX for the 2018-2022 period. The type of research used is quantitative method and the type of data is secondary data accessed through the official website of the Indonesia Stock Exchange (www.idx.co.id). The sampling technique used in this study was purposive sampling method with a total sample of 28 companies. The data analysis technique uses descriptive statistical analysis, classical assumption test, multiple linear analysis, coefficient of determination (R2) test, and hypothesis testing. The results of this study partially show that the Capital Structure variable has no significant effect on firm value as evidenced by the tcount < ttable (1.015 < 2.05183) with a significant value of 0.319 > 0.05. Investment decisions have a significant effect on firm value as evidenced by the results of tcount> ttable (2.540> 2.0518) with a significant value of 0.017 <0.05. Capital Structure and Investment Decision simultaneously have a significant effect on firm value as evidenced by the results of hypothesis testing which shows 0.014 <0.05 and comparison of fcount > ftabel, (5.019 > 3.35). The coefficient of determination test shows that the Adjusted R Square value (Coefficient of Determination) is 0.271. This means that the influence of the independent variables (Capital Structure and Investment Decision) is 27.1% and the remaining 72,9% is influenced by other variables